Letter to Jane Tolmach from Arthur Sylvester, Assistant Secretray of Defense - Arthur Sylvester:::::: (1961)
A letter to Jane Tolmach from Arthur Sylvester, Assistant Secretary of Defense, in regards to her concerns about the film "Communism on the Map."